Long Term Outcome of Avulsed Immature Mandibular Incisor with Progressive External Root Resorption: 9 Years Follow-Up - Lina Mickeviciene; Vestina Ciruliene; Greta Lodiene (Stilus Optimus, 2023)
Background: Avulsion of permanent teeth is the most common in young permanent dentition. Replantation of immature teeth after avulsion represents a major challenge in terms of treatment management and long-term prognosis. This case report describes 9 years of follow-up for an avulsed and replanted immature mandibular lateral incisor with progressive external root resorption. Methods: A 7-year-old patient following an accident in which his mandibular left central incisor was avulsed and replanted within one hour after being stored in a physiological storage medium. However, radiographic examination conducted six weeks after the dental injury revealed inflammatory root resorption of the replanted tooth #31. To address root resorption, endodontic treatment was performed involving the use of calcium hydroxide as an intracanal medication for a short period of time, followed by root canal obturation with mineral trioxide aggregate placed below the crestal bone margin. Results: Three months later the root resorption had progressed. Consequently, a decision was made to perform periodontal surgery. While the long-term follow-up revealed that the inflammatory root resorption had damaged half of the root, the tooth remained functional and aesthetically favourable. Conclusions: Despite the challenges associated with replantation of an immature tooth following avulsion, this case demonstrated favourable outcomes. The tooth maintained its functionality, exhibited favourable aesthetic, and the dimensions of the alveolar ridge were preserved, allowing for the physiological expansion of the dental arch.